Daikibo dēta kanri entāpuraizu ākitekucha no besuto purakutisu / = Data management at scale : - Strengholt, Piethein (Orairī Japan, 2022)
"As data management and integration continue to evolve rapidly, storing all your data in one place, such as a data warehouse, is no longer scalable. In the very near future, data will need to be distributed and available for several technological solutions. With this practical book, you'll learnhow to migrate your enterprise from a complex and tightly coupled data landscape to a more flexible architecture ready for the modern world of data consumption. Executives, data architects, analytics teams, and compliance and governance staff will learn how to build a modern scalable data landscape using the Scaled Architecture, which you can introduce incrementally without a large upfront investment. Author Piethein Strengholt provides blueprints, principles, observations, best practices, and patterns to get you up to speed. Examine data management trends, including technological developments, regulatory requirements, and privacy concerns Go deep into the Scaled Architecture and learn how the pieces fit together Explore data governance and data security, master data management, self-service data marketplaces, and the importance of metadata." --
Includes bibiographical references
Keywords: Database management; Electronic data processing -- Management; Information technology -- Management; Bases de données; Gestion; Technologie de l'information; Gestion; Electronic data processing; Management; Information technology; Management